1994
DOI: 10.1111/j.1749-6632.1994.tb19852.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Reservoir of Vibrio cholerae The Causative Agent of Choleraa

Abstract: BACKGROUNDUntil the late 1970s and early 1980s, Vibrio cholerae was believed to be highly host-adapted and incapable of surviving longer than a few hours or days outside the human intestine. This view, enunciated by Felsenfeld,' was that "some authors claimed that cholera vibrios may survive in water, particularly seawater, for as long as 2 months. This is, however, scarcely possible under natural conditions, if reinfection of the water does not take place." This perspective of cholera ecology dominated the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(166 citation statements)
references
References 32 publications
6
157
0
3
Order By: Relevance
“…The association of V. cholerae with zooplankton can protect the bacteria from environmental stresses and low nutrient levels and enhance their distribution in the environment. 7,8,34 The toxigenic V. cholerae detection data from this study are supported by the research results of Alam and others 6 who reported isolating the toxigenic V. cholerae O1 El Tor biotype from three water samples collected between April 2012 and March 2013 in the Ouest Department near the towns of Gressier and Leogane. However, other researchers, using only culture methods, did not isolate or detect toxigenic V. cholerae from water samples collected in July 2012 from 36 aquatic locations in the Ouest and Artibonite Departments.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The association of V. cholerae with zooplankton can protect the bacteria from environmental stresses and low nutrient levels and enhance their distribution in the environment. 7,8,34 The toxigenic V. cholerae detection data from this study are supported by the research results of Alam and others 6 who reported isolating the toxigenic V. cholerae O1 El Tor biotype from three water samples collected between April 2012 and March 2013 in the Ouest Department near the towns of Gressier and Leogane. However, other researchers, using only culture methods, did not isolate or detect toxigenic V. cholerae from water samples collected in July 2012 from 36 aquatic locations in the Ouest and Artibonite Departments.…”
Section: Discussionsupporting
confidence: 72%
“…The positive associations between DFA-DVC detections and salinity, temperature, and specific conductance are in concordance with the established paradigm of V. cholerae as autochthonous to the aquatic environment. 34 During this study, TCBS agar resulted in a significantly higher percentage of V. cholerae positive isolates compared with CV agar. However, these findings warrant further investigation; there are several brands of TCBS on the market and there are differences in performance between brands.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has also been shown to resist suboptimal conditions through specific associations of the bacterium with aquatic plants 10 or animals such as oysters, crabs and copepods. [11][12][13][14] As a result, the pathogen can persist for longer periods in aquatic habitats. Weather conditions such as an increase in environmental or sea surface temperatures favour plankton bloom.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a significant number of MTB genes that are essential for growth in macrophages are constitutively expressed. Unlike pathogens with environmental reservoirs like Salmonella typhi or Vibrio cholerae (22,23), MTB never resides outside of the human host and depends exclusively on transmission between humans for its continued survival (1). Constitutive expression of genes required for survival may be a necessary adaptation to a complex lifestyle in the host milieu.…”
Section: Gene Expression Analysis Is Poorly Predictive Of Requirementmentioning
confidence: 99%